THE ROLE OF WILAYAT AL-HISBAH IN THE IMPLEMENTATION OF ISLAMIC SHARIAH IN ACEH - Rusjdi Ali Muhammad (PETITA: JURNAL KAJIAN ILMU HUKUM DAN SYARIAH, 2017)
The Wilayat al-Hisbah (WH), known also as sharia police in Aceh, plays important roles in implementing Islamic law in Aceh - Indonesia. In one hand they must act professionally based on Islamic principles, unfortunately their future career is still unclear. In national level there are no clear regulations mentioning the WH career path. This consequence lead to the professionality of WH. Most of them will switch their career to another career, having clear future career. For the time being, in WH office will hard to get higher position. In national level, the career of WH does not have a stepping stone. Thus, most of government officer will chase other positions after five years. This fact have affected the implementation sharia law in Aceh Indonesia, caused by lack of WH officer in every years. Abstrak: Wilayat al-Hisbah (WH) yang juga dikenal sebagai polisi syariah di Aceh memainkan peran penting dalam menerapkan hukum Islam di Aceh - Indonesia. Di satu sisi mereka harus bertindak profesional berdasarkan prinsip-prinsip Islam, namun masa depan karir mereka masih belum jelas. Di tingkat nasional, tidak ada peraturan yang jelas mengenai jalur karir WH. Hal ini berdampak pada profesionalitas WH. Sebagian besar dari mereka akan beralih karir ke karir lain yang memiliki masa depan jelas. Untuk saat ini, sulit untuk mendapatkan posisi yang lebih tinggi di kantor WH. Sementara di tingkat nasional, karir WH tidak memiliki batu loncatan. Oleh karena itu, sebagian besar pejabat pemerintah akan mengejar posisi lain setelah lima tahun. Hal ini mempengaruhi implementasi Syariah islam di Aceh, Indonesia, disebabkan oleh kurangnya petugas WH setiap tahun. Kata kunci: Polisi Syariah, Jalur Karir, Syariah Islam, Pegawai Pemerintah